Pengaruh Model Kooperatif Tipe Think Pair Share (TPS) Terhadap Keaktifan Siswa Pada Mata Pelajaran Ipa Materi Kalor Dan Wujud Benda - Nurhasanah, Rosyifa Lala; Syar, Nur Inayah; Mahmudah, Istiyati (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2024)
This study aims to evaluate the efficacy of implementing the Think Pair Share (TPS) cooperative model in teaching science subjects pertaining to heat materials and object forms. Additionally, it seeks to assess the level of student engagement during the implementation of the TPS cooperative model in these science subjects. Lastly, it aims to examine the impact of the TPS cooperative model on student activity in science subjects related to heat materials and object forms. This study utilises an ex post facto research methodology, which is a quantitative approach. A commendable investigation carried out by students in the VA class. The study was carried out at MI Miftahul Huda 2 Palangka Raya. The data collection process utilises questionnaires, observation sheets, and documentation. Applying normality and hypothesis testing for the purpose of data analysis. (1) The use of the TPS collaborative model in the science subject of heat material and the shape of things resulted in an average score of 59.80%, which falls within the good range. The students' involvement in applying the TPS cooperative model in the science subject of heat material and the form of objects achieved an average of 65.91% in the exceptional category. The precondition test (3) investigates the influence of the cooperative model of the TPS type on student involvement in science courses, particularly in relation to thermal materials and object forms. A hypothesis test was conducted using a two-tailed significance threshold. Applying the TPS cooperative model to students' activities in science disciplines, notably heat matter and object shape, demonstrates a strong correlation with a Significance value of 0.001, which is below the threshold of 0.05.